Given that \( x = 2 \) is a zero of the polynomial \( f(x) = x^3 - 3x^2 - 10x + 24 \), we can use the Factor Theorem, which states that \( (x - c) \) is a factor of \( f(x) \) if \( f(c) = 0 \). Since \( x = 2 \) is a zero, \( (x - 2) \) is a factor of \( f(x) \).
Next, we will perform polynomial long division to divide \( f(x) \) by \( (x - 2) \) to determine the other factors.
Step 1: Polynomial Long Division
- Divide the leading term:
\[
\frac{x^3}{x} = x^2
\]
- Multiply:
\[
x^2(x - 2) = x^3 - 2x^2
\]
- Subtract:
\[
(x^3 - 3x^2) - (x^3 - 2x^2) = -x^2
\]
- Bring down the next term:
- Now the polynomial is \( -x^2 - 10x \).
- Repeat the process:
- Divide: \(\frac{-x^2}{x} = -x\)
- Multiply: \(-x(x - 2) = -x^2 + 2x\)
- Subtract:
\[
(-x^2 - 10x) - (-x^2 + 2x) = -12x
\]
- Bring down the last term:
- Now the polynomial is \( -12x + 24 \).
- Repeat:
- Divide: \(\frac{-12x}{x} = -12\)
- Multiply: \(-12(x - 2) = -12x + 24\)
- Subtract:
\[
(-12x + 24) - (-12x + 24) = 0
\]
Step 2: Summarize the division
Now we can express \( f(x) \) as:
\[
f(x) = (x - 2)(x^2 - x - 12)
\]
Step 3: Factor the quadratic \( x^2 - x - 12 \)
To factor \( x^2 - x - 12 \), we look for two numbers that multiply to \(-12\) and add to \(-1\). These numbers are \( -4 \) and \( 3 \).
Thus:
\[
x^2 - x - 12 = (x - 4)(x + 3)
\]
Final Factorization of \( f(x) \)
Putting it all together, we have:
\[
f(x) = (x - 2)(x - 4)(x + 3)
\]
Conclusion
The final factored form of \( f(x) \) is:
\[
f(x) = (x - 2)(x + 3)(x - 4)
\]
Therefore, the correct response is:
\( f(x) = (x - 2)(x + 3)(x - 4) \).